Network control for a multi-user transputer-based system. - Gerber, Aurona J (My University, 1991)
The MC2/64 system is a configureable multi-user transputer- based system which was designed using a modular approach. The MC2/64 consists of MC2 Clusters which are connected using a modified Clos network. The MC2 Clusters were designed and realised as completely configurable modules using and extending an algorithm based on Eulerian cycles through a requested graph. This dissertation discusses the configuration algorithm and the extensions made to the algorithm for the MC2 Clusters. The total MC2/64 system is not completely configurable as a MC2 Cluster releases only a limited number of links for inter-cluster connections. This dissertation analyses the configurability of MC2/64, but also presents algorithms which enhance the usability of the system from the user's point of view. The design and the implementation of the network control software are also submitted as topics in this dissertation. The network control software must allow multiple users to use the system, but without them influencing each other's transputer domains. This dissertation therefore seeks to give an overview of network control problems and the solutions implemented in current MC2/64 systems. The results of the research done for this dissertation will hopefully aid in the design of future MC2 systems which will provide South Africa with much needed, low cost, high performance computing power.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering
Keywords: Transputers.; Computer networks.